Study on code-switching: an analysis of pedagogical conversation / Nurul Azian Izzaty Azman - Azman, Nurul Azian Izzaty (Faculty of Education, 2014)
In order to adapt to and understand the context, code-switching often occurs by students who are less fluent and they have different patterns in their language of choice. Code-switching often occurs especially in their daily conversations. In ESL classroom, the pedagogical conversations between teachers and students and between students are often littered with a combination of the second language, first language and native language which is Bahasa Melayu. Thus, while in English classroom, the occurrences of different types of code-switching from the English teacher as well as the students are observed and analysed. The teacher's perceptions may reveal the functions and factors that influence the code-switching during teaching and learning process. Qualitative research is applied in this study to observe the participants besides to gain understanding of the English teacher and students faced during ESL classroom. Therefore, classroom observations and individual interview are conducted in order to obtain data. Two classroom observations, in a total of 80-minute each are recorded to examine the pedagogical conversation between the teacher and students and among the students as well. To get information about factors and perception on code-witching, individual interview with English teacher is conducted and is recorded too. One of the secondary schools in Port Klang is selected for this research and the participants involved are form two students and the English teacher. Understanding the types and observing the occurrences of code-switching allow the researcher to indicate each usage of code-switching by preparing the frequency table. For every five minutes, the occurrences of code-switching are checked to ensure its validity. All research questions are developed for this study in which both teacher and students use Intersentential code-switching most in their conversation, followed by Intrasentential, Borrowing and Tag-like code-switching. Lastly, the data shows that Caique is not used by participants during the English classroom.